PELANGGARAN HAM TERHADAP KEBEBASAN BERAGAMA: STUDI KASUS KONFLIK ANTAR AGAMA DI INDIA DAN INDONESIA - Khoerudin, Cahya Amai; Pandu Ardyaninggar, Pandu (Ilmu Hukum Prima (IHP), 2023)
Freedom of religion is something that is protected because it involves human rights. Human rights are contained in the Universal Declaration of Human Rights. However, some regulations regulate the fact that violations of freedom of religion have not only occurred once or twice but have occurred many times. India is one of several countries that experience conflicts regarding freedom of religion, especially between religions, namely Islam and Hinduism. This conflict culminated with the emergence of the ratification of the Amendment to the Indian Citizenship Act (CAB) in 2019 and caused a polemic of riots between Muslims and Hindus. The method of analysis used is a qualitative data analysis method. The research method carried out on the problem this time is the statute approach (statutory approach), case approach (case approach), and explorative research (things that have not been known before), which are all related to this research. Based on the findings of the research conducted and the data obtained that there is still discrimination against religious minorities both in India and Indonesia, the existence of human rights is very concerning. The implications can be achieved by increasing religious tolerance and increasing the importance of human rights, especially freedom of religion, providing a deterrent effect on human rights violators.